Pemilihan Konsentrasi Pengawet dan Kecepatan Rotasi Pengadukan terhadap Kualitas Produk Sirup Obat Asetaminofen “X” dengan Metode Desain Eksperimen - Johan K. Runtuk; Nanda Nurita (JIE Scientific Journal on Research and Application of Industrial System, 2017)
PT XYZ is one of the pharmaceutical companies in Indonesia. There is a problem in the quality of the stability of formulation in acetaminophen syrup "X", which is the problem of product deposition. Experiment was conducted to see the effect of change of concentration of preservative or thickener to product quality and to know how big influence of speed of stirring to product quality. The method used is Design Of Experiment (DOE) with 2 factors: concentration of preservative or thickening and stirring speed to centrifugation and viscosity response; and each factor has 3 levels, for concentration of preservative or thickeners level tested is 10%, 15% and 20% while for stirring the level tested is 200 RPM, 300 RPM, and 400 RPM. The test is a laboratory scale test and collected data then analyzed using full random design method and then calculated statistically using two-factor analysis of variance method (ANOVA) to see the effect between concentration of preservative or thickening and speed of stirring to syrup deposition. The best combination obtained is a preservative or thickening concentration of 20% and 300 RPM speed ofstirring.